Ortodontik bant ve diş arasında oluşan siman boşluklarının ve farklı bant simanlarının çözünürlüklerinin değerlendirilmesi / Evaluation of gaps beneath orthodontic bands and solubility of different band cements - ÇALIK KÖSELER, Berra (Bezmialem Vakıf University, 2017)
The purpose of this in vitro study is to evaluate the surface areas of gaps remaining beneath the orthodontic bands cemented with two different methods and different band cements, and compare the solubility and sorption characteristics of these band cements in oral acids and distilled water. In this study, orthodontic bands were cemented to standard sized ceramic tooth samples with conventional glass ionomer cement (Ketac Cem; 3M Espe, Gmbh, Seefeld, Germany), resin modified glass ionomer cement (Multi-Cure; 3M Unitek, Monrovia, California, USA) and polyacid modified glass ionomer cement (Transbond Plus; 3M Unitek, Monrovia, California, USA). After removing of the bands from the tooth surface, the samples were scanned with a three dimensional dental scanner and the surface areas of the gaps between the band and the tooth were measured with a three dimensional design program (SolidWorks 2016). Assessment of sorption and solubility characteristics of the same materials was performed by recording the weight changes of standard sized discs that were immersed in distilled water, lactic acid and propionic acid on the 1st, 7th and 28th days. The largest gaps were recorded in the samples cemented without the occlusal barriers for all three cements (p<0,05). Regardless of the bonding method, the surface areas of the gaps remained between the band and the tooth surface were found similar for conventional glass ionomer (Ketac Cem), resin modified glass ionomer (Multi-Cure) and polyacid modified glass ionomer (Transbond Plus) band cements (p>0,05). The results of the absorption and solubility tests showed that the highest solubility values were recorded for conventional glass ionomer cements and the lowest solubility values for the polyacid modified resin regardless of the storage media, but these results were not statistically significant (p>0,05). The highest sorption values were recorded for the resin modified cement ionomer cement (p <0.05). The highest solubility values were recorded in samples stored in a lactic acid media.
Thesis (dentistry)--Bezmialem Vakıf University, Faculty of Dentistry, Department of Orthodontics, Istanbul, 2017
Keywords: Ortodonti Anabilim Dalı; Ortodonti = Orthodontics; Department of Orthodontics; Diş Hekimliği = Dentistry